Pengaruh Kualitas dan Harga Produk Terhadap Minat Beli Produk Body Wash di Koperasi Yamughni - Syifa Nabilla; Raskadi (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2026)
The motivation behind this study is the increasing competition in body care products, which forces cooperatives to understand the factors influencing consumer purchase intentions. The purpose of this study is to investigate the partial and simultaneous effects of product quality and price on Yamughni Cooperative customers’ intentions to purchase body wash products. This study uses an explanatory, quantitative approach. Among the techniques used for data analysis are descriptive and verificative analysis employing multiple linear regression tests. The results of the study demonstrate that product quality has a positive and significant influence on purchase intention, with a t-value of 5.337 (sig=0.000) and a regression coefficient of 0.226. Price has a positive and substantial effect on purchase intention; the regression coefficient is 0.273, and the t-value is 3.724 (sig=0.000). With an F-value of 111.245 (sig=0.000), both product quality and price had a large simultaneous impact on purchase intention. This study shows that by improving product quality and setting the right price, cooperatives can boost consumer purchase intention.